(untitled) (Muitas Vozes, 2016)
This research reflects the experiences of language teachers regarding race and racism in their lives in Brazil. The three main research objectives were to examine how these teachers personally encountered racism; what these teachers’ narratives reveal about racism and the way that they reflect about their own racial identities; and finally, how the experiences of these teachers were transformed into action in their language classrooms and in their private lives. The theoretical framework used was based on Critical Race Theory (CRT), which was the basis for data analysis (LADSON-BILLINGS, 1998, LADSON-BILLINGS AND TATE, 1995). The methodology for data gathering was autobiographical narratives about these teachers’ experiences of race and racism. The results showed that in one way or other these teachers faced issues of race and racism in their own homes, in schools as students, in university as students, as well as in their own working environments.